Unveiling the formation of gradient microstructure in the magnesium alloy sheet fabricated via turned-bearing extrusion - Lintao Liu; Yan Song; Jieyu Li; Chao He; Shengwen Bai; Bin Jiang; Jiangfeng Song; Guangsheng Huang; Dingfei Zhang; Fusheng Pan (Journal of Materials Research and Technology, 2024)
On certain occasions, such as bending, a sheet with gradient microstructure may present higher formability compared to one with uniform microstructure. In this study, the formation of gradient microstructure in AZ31 alloy sheets extruded by the asymmetric die is comprehensively investigated. The results exhibit the microstructure evolution undergoes three stages, namely the initial dynamic recrystallization (DRX), abnormal grain growth (AGG), and the secondary DRX. After the initial DRX, the microstructure is fine and uniform, and the transverse direction (TD) preferred texture is formed due to the initiation of non-basal slip. Owing to the high extrusion temperature, AGG occurs after the initial DRX. The grains with basal texture are engulfed by the grains with TD-preferred texture. During the AGG, the grain size is coarsened from 11.4 μm to 382.1 μm. As the material flows through the die bearing, the secondary DRX occurs near the corner of the die. Ascribed to the gradient strain near the bearing, the grains near the bottom surface of the sheet are refined again, while those near the other side inherit the large sizes from grown grains. Ultimately, the extruded sheet exhibits gradient microstructure along the thickness direction, i.e. normal direction (ND). The gradient-distributed plastic strain and strain rate are the main causes of gradient microstructure.